Christian reconstruction : R.J. Rushdoony and American religious conservatism - McVicar, Michael J. (The University of North Carolina Press, 2015)
This is the first critical history of Christian Reconstruction and its founder and champion, theologian and activist Rousas John Rushdoony (1915-2001). Drawing on exclusive access to Rushdoony's personal papers and extensive correspondence, Michael J. McVicar demonstrates the considerable role Reconstructionism played in the development of the radical Christian Right and an American theocratic agenda.